Direct in situ nucleic acid amplification: control of artefact and use of labelled primers. Issue 6 (December 1996) - Ray, R; Sim, R; Khan, K; Cooper, P; Pounder, R; Wakefield, A
Abstract : Aims —To evaluate factors which ameliorate false positive artefacts with direct in situ PCR using labelled dNTPs; to investigate the use of labelled primers to overcome this artefact whilst maintaining sensitivity. Methods —Sections of measles (RNA virus) infected Vero cells with cytoplasmic signal or cytomegalovirus (DNA virus) infected fibroblasts with nuclear signal were collected. In situ PCR (or in situ RT-PCR) was carried out by methods permitting evaporation. Reagents or conditions which may control false positive artefacts using labelled dNTPs were investigated systematically. Labelled primers were tested to overcome artefacts, with adjuncts which improve sensitivity. Results —No reagent nor condition investigated was able to control the artefact with labelled dNTPs. Excessive digestion and incomplete DNAse treatments exacerbated the artefact, whereas novobiocin decreased both specific signal and artefact. However, the artefact was controlled by labelled primers, albeit with relatively low sensitivity. Sensitivity using labelled primers could be increased using alcohol fixation, albumin or Perfectmatch. Conclusions —A repair process is implicated for the artefact using labelled dNTPs. Excessive digestion or DNAse treatment may exacerbate DNA damage by disrupting histones or the DNA, respectively. Labelled primers control this artefact, albeit with reduced sensitivity, which may be improved by precipitation fixatives (alcohol) and reagents which enhance specific reaction.